Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain. Issue 12 (10th June 2016) - Goerig, Nicole L.; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel A.; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker; Rühle, Paul F.; Putz, Florian; Semrau, Sabine; et al.
Abstract: Background: Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain. Methods: Fifty patients requiring whole-brain radiotherapy for brain metastases ( n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas ( n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA. Results: Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection. In the group at risk consisting of anti-CMV IgG+ patients, age >65 ( P = .004) and the amount of dexamethasone taken during radio(chemo)therapy ( P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03–1.86; P = .25). Conclusion: CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.